2017
DOI: 10.18632/oncotarget.19630
|View full text |Cite
|
Sign up to set email alerts
|

PKM2 activation sensitizes cancer cells to growth inhibition by 2-deoxy-D-glucose

Abstract: Cancer metabolism has emerged as an increasingly attractive target for interfering with tumor growth. Small molecule activators of pyruvate kinase isozyme M2 (PKM2) suppress tumor formation but have an unknown effect on established tumors. We demonstrate that TEPP-46, a PKM2 activator, results in increased glucose consumption, providing the rationale for combining PKM2 activators with the toxic glucose analog, 2-deoxy-D-glucose (2-DG). Combination treatment resulted in reduced viability of a range of cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Combination treatment resulted in reduced viability of a range of cell lines in standard cell culture conditions. 41) Moreover, 2-deoxy-D-glucose competitively inhibited the production of G6P from glucose, which resembles that of PA. This study supported the beneficial effects of dual targeting of PA to PKM2 and HK2.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Combination treatment resulted in reduced viability of a range of cell lines in standard cell culture conditions. 41) Moreover, 2-deoxy-D-glucose competitively inhibited the production of G6P from glucose, which resembles that of PA. This study supported the beneficial effects of dual targeting of PA to PKM2 and HK2.…”
Section: Discussionmentioning
confidence: 87%
“…9) Moreover, ROS-mediated ER stress is associated with apoptosis initiation, which has been observed in PAtreated lung cancer cells. 4,40) In summary, ROS generation by PA may be a fundamental mechanism for the anti-cancer activity of PA.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with pancreatic cancer cells, the inhibition of PKM2 expression in the normal glucose medium did not affect cell growth and proliferation, whereas the suppression of PKM2 expression in low glucose (0.5mM) medium increased cell viability 18 . In another study with lung cancer cells, it was determined that induced PKM2 mRNA expression in low glucose medium increased cell proliferation 19 . In our study, we found that PKM2 expressions decreased significantly in low glucose medium in all cell lines we used.…”
Section: Discussionmentioning
confidence: 99%
“…Four recent reports have investigated the Lac/Pyr ratio (or k PL ). Ravoori et al and Tee et al found that this ratio increases, whereas Park et al and Iversen et al found it to remain stable, when a variety of preclinical tumours (glioma, mammary carcinoma, ovarian, lung carcinoma) respond to therapy. In References 33, 35 and 36, the therapeutic agent used displayed anti‐angiogenic or vascular disrupting activity, while in Reference the drug used was an activator of PKM2.…”
Section: Mrs(i)‐detectable Metabolic Hallmarks Of Cancer: Applicationmentioning
confidence: 99%
“…Ravoori et al and Tee et al found that this ratio increases, whereas Park et al and Iversen et al found it to remain stable, when a variety of preclinical tumours (glioma, mammary carcinoma, ovarian, lung carcinoma) respond to therapy. In References 33, 35 and 36, the therapeutic agent used displayed anti‐angiogenic or vascular disrupting activity, while in Reference the drug used was an activator of PKM2. The rationale to explain this initially conflicting evidence is essentially put forward in References 33 and 36: anti‐angiogenic agents will produce hypoxic regions in the tumour, causing increased glycolytic flow to maintain required ATP (adenosine triphosphate) production by the tumour cell, overriding the decreased demand of carbon precursors for cell duplication by the growth‐arrested tumour cells.…”
Section: Mrs(i)‐detectable Metabolic Hallmarks Of Cancer: Applicationmentioning
confidence: 99%